DIGITAL MARKETING STRATEGIES SUPPORTING COMMUNITY ACTION IN PLASTIC BAG REDUCTION: Case of Banjarmasin City - Zarqan, Ince Ahmad; Nugraha, Dimas Yudistira; Sihotang, Fernando; Nababan, Adli Abdillah; Irwansyah, Irwansyah (Bina Nusantara University, 2026)
Plastic waste has been and still is a pressing environmental concern in Indonesia, especially with single-use plastic bags that continue to cause river and ocean pollution. The city of Banjarmasin in Indonesia was the first to enact a policy banning single-use plastic bags in contemporary retail outlets. The purpose of this research was to understand how marketing on the Internet could further aid this environmental community project and promote positive changes in behavior. The research used qualitative methods and the case study and netnography approaches. Data were gathered from the local social media campaigns which included in-depth interviews with 40 respondents from different categories namely consumers, minimarket managers, influencers and policymakers, 4 focus group discussions, and interactions. Thematic analysis showed that while digital campaigns raised public awareness and knowledge of the problem, the absence of strong, habitual behavioral change was a huge challenge. The use of religious and cultural framing was effective in strengthening the message, especially when constricted by local micro-influencers with relatable community ties. People were able to use digital nudges installed in e-commerce checkout systems and point of sale systems in minimarkets to engage in easy behaviors like buying reusable bags. However, cost perceptions, habitual reliance on single-use plastics, and the digital divide among older generations were still major barriers. All things considered, the results underscored the need for integration of digital marketing with enforcement of policy as well as public outreach for effective impact. This study found that the policy framework for the environment can be supplemented with digital marketing focused at awareness raising, intention mobilization, and actual behavior change, and its use in community service projects is crucial for enduring sustainability.